Profile and working conditions of dental assistants in Marikina City - Banzon, Marie Cristine Denise; Rosario, Theresa Marie; Aquino, Angelita Galban
Introduction. A dental assistant is expected to be responsible for a variety of duties in the dental office. As ascertained by their title, a dental assistant will assist the dentist during procedures and performs laboratory work and clerical duties. This study aimed to describe the profile of dental assistants in Marikina City.
Methods. A survey was done last December 2012 to dentists and dental assistants in Marikina City via one stage cluster sampling. 8 barangays were randomly selected out of 16. All clinics participated in the study. Answers of the 96 respondents, which included dentists and assistants, were encoded, tabulated and interpreted through mean frequency distribution and percentages.
Results. It was revelat that 60% of dental clinics in Marikina City employ a dental assistants. Dentists preferred their assistants to be between ages 18-24 years, and did not have a specific gender preference. Incidentally, most dental assistants were 18-24 years old, single, female and reached college level. All assistants received training from their dentist employers. Duties included chairside assisting, laboratory tasks and clerical duties.
Conclusion. Based on the results of the study, it can be concluded that dental assistants in Marikina City follow minimal demographic profile in terms of education and training, which is not proportionate to the big duties and responsibilities being expected of them.
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Dental assistants